2020
DOI: 10.21037/atm-20-5963
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical and pathological features of primary bilateral macronodular adrenocortical hyperplasia compared with unilateral cortisol-secreting adrenal adenoma

Abstract: Background: Primary bilateral macronodular adrenocortical hyperplasia (PBMAH) is a rare condition with untypical subclinical symptoms of Cushing's syndrome (CS). This study aimed to compare the clinical and pathological features of PBMAH with unilateral cortisol-secreting adrenal adenoma (UAA).Methods: We prospectively included 46 PBMAH patients and 205 UAA patients from January 2000 to February 2014. Cortisol levels and 24 hours urine free cortisol (UFC) were determined at baseline and during dexamethasone su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…29 Furthermore, in a study conducted by Zhang | 103 and hypertension were identified at a higher rate in the PBMAH than UAA, despite the fact that the patients with unilateral adenoma contained more cases of overt CS. 6 On the other hand, Morelli et al 30 investigated patients with subclinical hypercortisolism in both bilateral and UAA groups and no significant differences in dyslipidemia or T2DM were observed. However, Morelli et al…”
Section: Dhea-s In Patients With Bilateral and Unilateral Macronodula...mentioning
confidence: 99%
“…29 Furthermore, in a study conducted by Zhang | 103 and hypertension were identified at a higher rate in the PBMAH than UAA, despite the fact that the patients with unilateral adenoma contained more cases of overt CS. 6 On the other hand, Morelli et al 30 investigated patients with subclinical hypercortisolism in both bilateral and UAA groups and no significant differences in dyslipidemia or T2DM were observed. However, Morelli et al…”
Section: Dhea-s In Patients With Bilateral and Unilateral Macronodula...mentioning
confidence: 99%
“…Hormonal characterization includes clinical symptoms of Cushing syndrome, often associated with autonomous cortisol secretion and presentation of ACTH-independent hypercortisolism. Because hypercortisolism usually develops slowly and radiologic imaging lacks specificity, PBMAH diagnosis is challenging and often delayed [26]. However, the improvement of diagnostic methods for adrenal incidentalomas increased the frequency of PBMAH diagnosis, which advanced the understanding of the clinical heterogeneity of this disease.…”
Section: Primary Bilateral Macronodular Adrenal Hyperplasiamentioning
confidence: 99%
“…Other authors reported suppressed ACTH levels only in 30% of the cases (48). The dexamethasone-CRH test is not useful for the differential diagnosis of ACTH dependence since it can cause false positives in a high percentage of bilateral adrenal lesions (~40% of the cases) (50).…”
Section: Biochemical Diagnosismentioning
confidence: 99%
“…Moreover, in patients with hypertension and/or hypokalemia, primary hyperaldosteronism should also be discarded. In addition, since these are bilateral lesions, adrenal insufficiency should be evaluated if there is suspicion of malignant or infiltrative disease, and of CAH (46,48).…”
Section: Biochemical Diagnosismentioning
confidence: 99%